Intervenção para o perdão em apenados - Alencar, Thalita Lays Fernandes de (2017)
This study is based on Enright‟s interpersonal forgiveness theory, who conceive forgiveness as a moral attitude and propose its study in three dimensions: forgiving another - dimension of the victims, and receiving forgiveness and self-forgiveness - dimensions of offenders. For each dimension are proposed clinical processes that have a similar structure composed of four phases: uncovering, decision, work and outcome. This dissertation is an intervention work with the aim of promoting attitudes to receiving forgiveness and self-forgiveness in a group of inmates. The intervention was based on the phases and units of the clinical processes and was performed in 16 sessions each lasting approximately 90 minutes. A quasi-experimental design was used with two groups submitted to pretest and posttest: an experimental group that received the intervention treatment and a control group that received no treatment. Participants were 10 male inmates in semi-open regime, with five participants in the experimental group, ages ranged from 28 to 47 years, and five participants in the control group, ages ranged from 22 to 37 years. Measures of Receiving Forgiveness, Self-forgiveness, Social Desirability, Vulnerability, Anxiety, Depression and Self-Esteem were used. The results showed that the experimental group showed significant differences from pretest to posttest in the following variables: attitude to receiving forgiveness, social desirability, vulnerability and anxiety. The Jacobson and Truax method was used to individually analyze participants in the experimental group, evaluating the changes that can be reliably attributed to the intervention and the clinical significance of this change, that indicates if they are strong enough to be considered relevant. Were found reliably improvement of four participants in atitude to receive forgiveness, of two participants in atitude to self-forgiveness, of three participants in self-esteem, of two participants in vulnerability, and of one participant in depression. All changes in the attitude of receiving forgiveness, atitude to self-forgiveness, and self-esteem were clinically significant. The best results with the dimension receiving forgiveness were expected, since literature points out that the self-forgiveness process is the most difficult among the three dimensions of forgiveness. The results indicated that this study partially achieve the objective of contributing to significant advances in the promotion of forgiveness and to the improvement of the well-being of the intervention participants. It is considered that the skills and strategies worked may help participants in their interpersonal relationships and conflict resolution.